0135 Self-Reported Sleep and Gut Microbiome Composition and Diversity: Associations in Well-Functioning Older Adults. (27th May 2020) - Holingue, C; Mueller, N T; Tanaka, T; Differding, M K; Chia, C W; Wu, M N; Schrack, J A; Simonsick, E M; Spira, A P
Abstract: Introduction: The gut microbiome is believed to play an important role in health and disease, yet little is known about the link between sleep and the gut microbiome in humans. We investigated the association of self-reported sleep with gut microbiome composition and diversity in a cohort of well-functioning older adults. Methods: We studied 791 participants (mean age = 71.5±12.0 years, 55% women) in the Baltimore Longitudinal Study of Aging with self-report sleep measures and whole-genome DNA sequencing of stool samples. Predictors (modeled as continuous variables) included insomnia symptoms from the Women's Health Initiative Insomnia Rating Scale (WHIIRS), sleep duration (<5, 5–6, 6–7, >7 hours), and frequency of excessive daytime sleepiness (EDS). We tested their association with gut microbiome diversity (Shannon index) and relative abundance of individual taxa using Kendall Tau Correlation. Next, we assessed whether these sleep variables were associated with overall microbiome structure (Bray-Curtis), adjusting for age, sex, race, education, BMI, depressive symptoms, and number of comorbidities. Results: Sleep duration was associated with overall microbiome composition (p<0.01), with longer sleep duration associated with lower biodiversity of microbes in the gut (p<0.05). In phylum-level analyses, higher WHIIRS total (i.e., more severe insomnia) was associated with lower relative abundance of Actinobacteria, while more frequent EDS was associated with lower relative abundance of Fusobacteria. More frequent trouble falling asleep, staying asleep, early waking, poorer sleep quality and higher WHIIRS total were associated with lower abundance of Synergistetes (all p<0.05). Conclusion: In well-functioning older adults, self-reported sleep duration, symptoms of insomnia, and EDS were associated with microbiome diversity and composition. The phylum Synergistetes, which has been associated with protective humoral immune response in prior literature, may be an important correlate of insomnia symptoms in older adults. Future investigations are needed to examine the gut microbiome as a driver or mediator of sleep-health associations. Support: This study was supported in part by National Institute on Aging (NIA) grant R01AG050507, the NIA Intramural Research Program (IRP), and Research and Development Contract HHSN-260-2004-00012C.